IMPLEMENTASI KURIKULUM MERDEKA MELALUI METODE BELAJAR MONTESSORI PADA PENDIDIKAN ANAK USIA DINI (PAUD) PERCONTOHAN PLAMBOYAN 3 KARAWANG - Syaharani, Nur Aisyah; Dewi, Ratnasari; Pujiarto, Pujiarto (IKIP Siliwangi, 2025)
Early childhood education must be implemented using the right approach, in order to support the cognitive, affective and psychomotor abilities of students. Therefore, a curriculum and learning methods are needed that must be relevant to interconnected science. This study aims to describe the implementation, supporting and inhibiting factors, and the results of the application of the independent curriculum through the Montessori learning method at PAUD Perpilot Plamboyan 3 Karawang. The independent curriculum emphasizes learning activities using the concept of